Risk factors for implant failure of intertrochanteric fractures with lateral femoral wall fracture after intramedullary nail fixation. Issue 11 (November 2021) - Fan, Jixing; Xu, Xiangyu; Zhou, Fang; Zhang, Zhishan; Tian, Yun; Ji, Hongquan; Guo, Yan; Lv, Yang; Yang, Zhongwei; Hou, Guojin
Highlights: The comminution extent of the LFW fracture might influence the stability of intertrochanteric fractures; CT scan was an efficient tool to identify fracture type of the lateral femoral wall; The intramedullary fixation might be an effective treatment method; Poor reduction quality and loss of medial support could increase the risk of implant failure Abstract: Introduction: Few studies have specifically evaluated the comminution extent of lateral femoral wall (LFW) fracture and risk factors of implant failure in intertrochanteric fractures with LFW fracture. The aim of present study was to evaluate the influence of comminution extent of LFW fracture on implant failure and identify risk factors of implant failure in cases with LFW fracture after intramedullary fixation. Methods: This retrospective study included 130 intertrochanteric fracture with LFW fracture treated with intramedullary fixation at a teaching hospital over a 13-year period from January 2006 to December 2018. Demographic information, cortical thickness index, the reduction quality, status of medial support, position of the screw/blade and status of lateral femoral wall were collected and compared. The logistic regression analyzes was performed to evaluate risk factors of implant failure in intertrochanteric fractures with LFW fracture after intramedullary nail fixation. Results: 10 patients (7.69%) suffered from mechanical failure after intramedullary fixation. Univariate analyzes showed that comminuted LFW fracture (OR, 7.625; 95%CI, 1.437~40.446; p  = 0.017), poor reduction quality (OR, 49.375; 95%CI, 7.217~337.804; p  < 0.001) and loss of medial support (OR, 17.818; 95%CI, 3.537~89.768; p  < 0.001) were associated with implant failure. After adjustment for confounding variables, the multivariable logistic regression analyzes showed that poor reduction quality (OR, 11.318; 95%CI, 1.126~113.755; p  = 0.039) and loss of medial support (OR, 7.734; 95%CI, 1.062~56.327; p  = 0.043) were independent risk factors for implant failure. Whereas, comminuted LFW fracture was not associated with implant failure ( p  = 0.429). Conclusions: The comminution extent of the LFW fracture might influence the stability of intertrochanteric fractures; and intramedullary fixation might be an effective treatment method. Furthermore, poor reduction quality and loss of medial support could increaze the risk of implant failure in intertrochanteric fractures with LFW fractures after intramedullary fixation. Therefore, we should pay great emphasis on fracture reduction quality in future.